Staphylococcus aureus activates NRLP3-dependent IL-1β secretion from human conjunctival goblet cells using α toxin and toll-like receptors 2 and 1 - Li, Dayu; Hodges, Robin; AukrustNaqvi, Maria; Bair, Jeffrey; Bispo, Paulo J. M.; Gilmore, Michael S.; Gregory-Ksander, Meredith; Dartt, Darlene A. (Frontiers in Cellular and Infection Microbiology, 2023)
We used cultured human conjunctival goblet cells to determine: (i) whether toxigenic S.aureusinduced activation of the epithelial goblet cells requires two signals to activate the NLRP3 inflammasome, (ii) if one signal is mediated by TLRs 1, 2, or 6; and (iii) if the S. aureus toxin a toxin is another signal for the activation of the inflammasome and secretion of mature IL-1b. Cultured cells were incubated with siRNA to knock down the different TLRs. After stimulation with toxigenic S. aureus RN6390, pro-IL-1b synthesis, caspase-1 activity, and mature IL-1b secretion were measured. In a separate set of experiments, cells were incubated with toxigenic S. aureus RN6390 or mutant S. aureus ALC837 that does not express a toxin with or without exogenous a toxin. A gentamicin protection assay was used to determine if intracellular bacteria were active. We conclude that a toxin from toxigenic S. aureus triggers two separate mechanisms required for the activation of the NLRP3 inflammasome and secretion of mature IL-1b. In the first mechanism a toxin secreted from internalized S. aureus produces a pore, allowing the internalized bacteria and associated PAMPs to interact with intracellular TLR2 and to a lesser extent TLR1. In the second mechanism a toxin forms a pore in the plasma membrane, leading to an efflux of cytosolic K + and influx of Ca 2+ . We conclude that a-toxin by these two different mechanisms triggers the synthesis of pro-IL-1b and NLRP3 components, activation of capase-1, and secretion of mature IL-1b to defend against the bacterial infection.